COVID-19 vaccine: vaccinate the young to protect the old? - Giubilini, A; Savulescu, J; Wilkinson, D (Oxford University Press, 2020)
When we have a vaccine against COVID-19, who should be vaccinated first? The question is relevant because, initially, vaccine availability will likely be limited. After healthcare and some other essential workers, it might seem the most obvious candidates are the elderly and other groups that are more vulnerable to the virus. However, we argue that this is not necessarily the case. Protecting the most vulnerable might require prioritizing vaccinating children in order to maximize the benefits of indirect immunity for the elderly and the other vulnerable groups. Whether this will be the best strategy from a public health perspective will depend on characteristics of the vaccine and of the virus, which are currently unknown. Here, we assess this possibility from an ethical point of view, by drawing comparisons and analogies with the case of the flu vaccination and with other examples of health policies and practices. We conclude that there are strong ethical reasons to vaccinate the young to protect the old, provided that the risks imposed on children are reasonable, even if that implies using children as a means to protect the elderly and the vulnerable.